Development of life skills guidance program for mosque youth - Arisanti, Risa; Rahman, Imas Kania; Hafidhuddin, Didin; Ibdalsyah, Ibdalsyah (Eximia, 2023)
This study aims to develop a mosque youth guidance program to build empirically tested life skills competence. The method used is research and development or Research and Development (R&D) with the ADDIE model. The stages of the research consisted of (1) Analysis of the needs of developing a mosque youth guidance program, (2) Design of a mosque youth guidance program, and (3) Program feasibility study. Needs analysis was carried out in two ways, namely by analyzing youth needs using the survey method, and analyzing existing mosque youth guidance programs. The design of the mosque youth life skills guidance program was made based on the results of needs analysis data and related theories. Furthermore, the feasibility study of the guidance program was carried out by expert validation tests (linguists, mosque youth advisor, psychologists and counselors), conducting Focus Group Discussions (FGD) on mosque youth groups (users, administrators, and mosque youth coaches) and evaluated by Indonesian Mosque Council. The results of the research were in the form of life skills guidance program for mosque youth who had passed the due diligence.